Larval features illuminating adult taxonomy? Case study in the European cardinal beetle species of the genus Pyrochroa (Coleoptera: Pyrochroidae: Pyrochroinae) - Molfini, Marco; Giulio, Andrea Di; Mancini, Emiliano; Bologna, Marco A. (Zootaxa, 2021)
Larvae of the two European species of the genus Pyrochroa (P. coccinea and P. serraticornis) are redescribed, for the first time based on Italian samples, and new relevant and distinctive characters have emerged from P. serraticornis. Particularly, the presence of a single urogomphal pit between urogomphi (representing a new condition for the entire family), and new characters of mandibles, open new questions about the current taxonomic status of the European species.